(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the present study was to study the job satisfaction and teacher effectiveness of undergraduate college teachers during online education process. For the study the sample of 400 undergraduate college teachers, 200 males and 200 females were selected from the government and private colleges of Raipur district of Chhattisgarh state through random sampling method. The data was collected with the help of teacher’s job satisfaction scale developed by Y.Mudgil, J.S.Mathur and Prabha Bhatia, and teacher effectiveness scale developed by Shallu Puri and S.C.Gakhar. For the analysis of data mean, standard deviation and t-test was used. The findings of the study revealed that the government UG teachers are more effective in their teaching when compared to private UG teachers and the government UG college teachers are far more satisfied with their job in comparison to the private UG college teachers during online education process.